Growth and development of Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) on corn flours (Bangladesh Journal of Zoology, 2010)
The present investigation deals with the effects of corn flour (varieties: NK-40, BARI-5, Khai-Vutta and Hera) on the growth and development of the red flour beetle Tribolium castaneum (Herbst). Corn flours produced lighter larvae, pupae and adults in comparison with the control (Wheat+yeast). Corn flours also significantly (P